2016
DOI: 10.1515/cclm-2015-1191
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic change of the systemic immune inflammation index predicts the prognosis of patients with hepatocellular carcinoma after curative resection

Abstract: The dynamic change and serial monitoring of the SII represent new indicators for predicting the early recurrence of HCC determining advance optimal therapy in advance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 38 publications
3
63
0
Order By: Relevance
“…Tumor size and tumor number were most important indicator of tumor burden. The two factors greatly impacted the prognosis of HCC after LT and surgical resection [18,19]. Consistent with previously published studies, poor differentiation was related to high incidence of recurrence and poor survival after hepatecomy or after transplantation [20].…”
Section: Discussionsupporting
confidence: 84%
“…Tumor size and tumor number were most important indicator of tumor burden. The two factors greatly impacted the prognosis of HCC after LT and surgical resection [18,19]. Consistent with previously published studies, poor differentiation was related to high incidence of recurrence and poor survival after hepatecomy or after transplantation [20].…”
Section: Discussionsupporting
confidence: 84%
“…Several inflammation prognostic scores, such as the systemic immune-inflammation index (SII), the neutrophil to lymphocyte ratio (NLR), the platelet to lymphocyte ratio (PLR) and the aspartate aminotransferase-lymphocyte ratio index (ALRI), have been developed to predict survival and recurrence in patients with HCC [14][15][16][17][18][19][20][21][22][23].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The relationship between the tumor and in ammation has been studied widely, tumors can lead to in ammation, which can cause the damage of DNA and micro-metastasis lesions[9], the systemic in ammatory response (SIR) can weaken the immune function of body and promote the progression of tumor. Related research found that neutrophils, lymphocytes and platelets can play a signi cant role in the SIR which are related the development of tumor [10,11], based on peripheral lymphocytes, neutrophils, and platelet count, Several systemic in ammation-based scores such as the combination of NLR and PLR(NLR-PLR) [12], the combination of platelet count (PLT) and NLR (PLT-NLR) [13], the systemic immunein ammation index (SII) can re ect the in ammation and immune status of human body [14,15], their prognostic value have been con rmed in some tumors. There is little clinical research had been published to compare the prognostic value of these in ammatory markers.…”
Section: Introductionmentioning
confidence: 99%